The Influence of Reading The Quran on Speech Development Cerebral Palsy - Siti Annoora Niroha Pulungan; Riksma Nurahmi Rinalti Akhlan (Asian Journal of Social and Humanities, 2023)
The image of a neuro-impaired child is very easily a child with cerebral palsy. Cerebral palsy or commonly abbreviated as CP has three levels of conditions, which are severe, moderate, and mild CP. The author discusses matters related to reading the Quran to the development of cerebral palsy speech. Aims to expose the influence of Reading the Quran on objects. The results of the discussion will explain the influence of reading the Quran on the development of cerebral palsy speech